2020
DOI: 10.1136/neurintsurg-2020-016380
|View full text |Cite
|
Sign up to set email alerts
|

Environmental sustainability in neurointerventional procedures: a waste audit

Abstract: BackgroundOperating rooms contribute between 20% to 70% of hospital waste. This study aimed to evaluate the waste burden of neurointerventional procedures performed in a radiology department, identify areas for waste reduction, and motivate new greening initiatives.MethodsWe performed a waste audit of 17 neurointerventional procedures at a tertiary-referral center over a 3-month period. Waste was categorized into five streams: general waste, clinical waste, recyclable plastic, recyclable paper, and sharps. Our… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
18
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 14 publications
0
18
0
2
Order By: Relevance
“…Neurointerventional procedures produced an average of 8 kg of waste per case (Shum et al, 2020). Hence, it is important for IR practitioners to re ect on their practice, change and re ne practice and engage in green policy to combat the issue of waste and prioritise environmental sustainability.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Neurointerventional procedures produced an average of 8 kg of waste per case (Shum et al, 2020). Hence, it is important for IR practitioners to re ect on their practice, change and re ne practice and engage in green policy to combat the issue of waste and prioritise environmental sustainability.…”
Section: Discussionmentioning
confidence: 99%
“…Chawla et al suggested the use of default double-sided printing for all printers, the use of recycled papers and envelopes, reduced printing of request forms, provision of scrap paper for internal notes and use of digital notepads (Chawla et al, 2017). An audit of waste generated during neurointerventional procedures found that a signi cant amount of paper, cardboard packaging and user manuals were produced (Shum et al, 2020). These were never read and go straight into the general or recyclable bin (Shum et al, 2020).…”
Section: Costmentioning
confidence: 99%
See 1 more Smart Citation
“…За кількістю відходів перше місце посідає ендоваскулярна оклюзія аневризми (13,1 кг), друге -ендоваскулярна емболізація мальформацій (10,3 кг), третє -механічна тромбектомія (8,8 кг), четверте -церебральна ангіографія (5,1 кг). Утилізація цих відходів є тягарем для лікарні, адже її вартість у 10-20 разів перевищує утилізацію простого сміття [6,7].…”
Section: дискусії та обговоренняunclassified
“…Man darf also durchaus von einem "Mülltsunami" durch die Medizin sprechen. Dabei ist insbesondere die Entsorgung von kontaminiertem Biomüll energieaufwendig (mit hoher CO 2 -Produktion), teuer (10-25-fach im Vergleich zu normalem Hausmüll) und führt in nicht unerheblichen Ausmaß zu toxischen Abgasen (wie Dioxin) [8].…”
unclassified